2010
DOI: 10.1186/1471-2377-10-12
|View full text |Cite
|
Sign up to set email alerts
|

The association between use of electronic media and prevalence of headache in adolescents: results from a population-based cross-sectional study

Abstract: BackgroundUse of electronic media, i.e. mobile phones, computers, television, game consoles or listening to music, is very common, especially amongst adolescents. There is currently a debate about whether frequent use of these media might have adverse effects on health, especially on headaches, which are among the most-reported health complaints in adolescents. The aim of the present study was to assess associations between frequent use of electronic media and the prevalence of different types of headache in a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
47
1
3

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(57 citation statements)
references
References 41 publications
5
47
1
3
Order By: Relevance
“…Epidemiological studies in children and adolescents have identified a whole variety of risk factors for headache (3,4,(11)(12)(13). These studies highlight the contribution of stress and lifestyle factors to any headache disorder, with a larger influence in migraineurs (12,14).…”
Section: Introductionmentioning
confidence: 99%
“…Epidemiological studies in children and adolescents have identified a whole variety of risk factors for headache (3,4,(11)(12)(13). These studies highlight the contribution of stress and lifestyle factors to any headache disorder, with a larger influence in migraineurs (12,14).…”
Section: Introductionmentioning
confidence: 99%
“…Among adolescents, prevalence rates of daily television and computer use are as high as 85 and 95%, respectively (Milde-Busch et al, 2010). Moreover, 72% of all internet users report using online social networking (Brenner, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Devices such as cell phones, computers, electronic games, tablets and TV have been used both for school purposes and leisure 2,3 . Due to easy access to electronic devices more time is spent with them and, as a consequence, negative impact on adolescents' health have been reported in the literature, such as sleep changes, tiredness, anxiety, depression, overweight, de-ORIGINAL ARTICLE DOI 10.5935/1806-0013.20150049 creased levels of physical activities, decreased concentration, musculoskeletal pain, stress and headache [3][4][5][6][7] .…”
Section: Introductionmentioning
confidence: 99%
“…Devices such as cell phones, computers, electronic games, tablets and TV have been used both for school purposes and leisure 2,3 . Due to easy access to electronic devices more time is spent with them and, as a consequence, negative impact on adolescents' health have been reported in the literature, such as sleep changes, tiredness, anxiety, depression, overweight, de-ORIGINAL ARTICLE DOI 10.5935/1806-0013.20150049 creased levels of physical activities, decreased concentration, musculoskeletal pain, stress and headache [3][4][5][6][7] . Headache, pointed as an increasing problem among children and adolescents and which is possibly related to changes in lifestyle and stress-related factors 8 , has been highlighted by some studies as a major complaint among adolescents due to the excessive use of electronic devices 6,9 .…”
Section: Introductionmentioning
confidence: 99%